The Burden of Disease in Personality Disorders: Diagnosis-Specific Quality of Life - Soeteman, Djøra I.; Verheul, Roel; Busschbach, Jan J.V. (Journal of personality disorders, 2008)
A generic quality of life measure was used to investigate the burden of disease in a large sample of patients with personality disorders. The 1,708 subjects included in this study were recruited from six different mental health care institutes in the Netherlands. The burden of disease was measured using the EuroQol EQ-5D. Personality disorders were diagnosed using the Structured Interview for DSM-IV Personality (SIDP-IV). The mean EQ-5D index value was 0.56. Primarily the total number of personality disorder diagnoses rather than the specific type determined the quality of life. Notably borderline personality disorder was not associated with the highest burden. The findings indicate that patients with personality disorders experience a high burden of disease, comparable to that of severe somatic illnesses. The results call into question the primary focus in literature on borderline personality disorder. The current study yields a strong argument in favor of reimbursing (effective) treatments for this patient population.